Experimental performance of unbonded polyester and carbon fiber reinforced elastomeric isolators under bidirectional seismic excitation - Losanno, Daniele; Madera Sierra, Ingrid E.; Spizzuoco, Mariacristina; Marulanda, Johannio; Thomson, Peter (Engineering structures, 2020)
The development of low-cost isolation systems should be a priority for the mitigation of seismic risk in earthquake prone areas of developing countries. In this paper, innovative Polyester Fiber Reinforced Elastomeric Isolators (P-FREIs) in unbonded configuration are proposed as a low-cost alternative to Carbon Fiber Reinforced Elastomeric Isolators (C-FREIs). An investigation of unbounded P-FREIs to evaluate their experimental performance compared to C-FREIs was performed using bidirectional shaking-table tests. Different devices were designed and subsequently manufactured in Colombia, South America, for several ground motions representative of regions in Italy with a moderate to high seismic risk. After preliminary characterization tests confirmed the satisfactory behavior of the samples in both compression and shear, bidirectional shaking-table tests were performed on a steel frame mock-up. Input motions were applied to assess the isolators’ behavior during real earthquakes and scaled up to the full contact of the originally vertical face with horizontal support. The isolators had a satisfactory response under these extreme conditions, with good recentering capabilities and negligible residual damage. The results of the experiments demonstrate the feasibility of the proposed technology, thanks to significant acceleration, inter-story drift and base shear mitigation. The performance of P-FREIs versus C-FREIs forms the basis for further development on the subject.